PHARMACOEPIDEMIOLOGICAL BASIS FOR THE USE OF ANTIBACTERIAL DRUGS FOR COMMUNITY-ACQUIRED PNEUMONIA IN CHILDREN OF DIFFERENT AGES IN A MODERN INTERPRETATION - Shakhlo Salokhitdinovna, Kodirova (PT. Antis International Publisher, 2025)
Objective: This study addresses the urgent issue of rational antibiotic therapy for pneumonia, focusing on improving the effectiveness of treatment and minimizing negative consequences. Despite the availability of various antibacterial agents, pneumonia incidence and complications continue to rise. Methods: The study examines two main trends in antibiotic selection for pneumonia: 1) the use of selective drugs to ensure a rational and cost-effective approach, minimizing disruption to the patient's saprophytic flora, and reducing the risk of superinfection and immunosuppressive effects; 2) empirical prescription of broad-spectrum antibiotics. Results: Findings highlight the effectiveness of selective antibiotics in reducing adverse outcomes, while broad-spectrum antibiotics are commonly used in empirical treatments. However, overuse of broad-spectrum agents may lead to resistance and other complications. Novelty: The research emphasizes the importance of rational antibiotic selection, advocating for selective drugs over broad-spectrum antibiotics to reduce the risk of resistance, improve patient outcomes, and avoid unnecessary side effects. This approach proposes a more targeted and economical method of managing pneumonia, offering a potential solution to the rising incidence and worsening consequences.